Titanium-aluminum alloy, method for manufacturing the same, and alloy material
Patent Information
- Application Number
- CN202611401258.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种钛铝系合金及其制备方法以及合金材料,旨在解决现有钛铝系合金成分配比不佳引发的力学性能不稳定、强韧协同性差、耐腐蚀性不足的技术问题
本发明公开了一种钛铝系合金及其制备方法以及合金材料,通过优化合金成分配比、定制化制备工艺及改良包套挤压成型工艺,优化钛铝系合金综合性能,适配航空航天高端应用场景。
Smart Images

Figure CN122979705A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium-aluminum alloy materials and plastic processing technology, and particularly to a titanium-aluminum alloy, its preparation method, and the alloy material. Background Technology
[0002] Titanium-aluminum alloys possess comprehensive advantages such as low density, high specific strength, and excellent high-temperature resistance, making them key lightweight structural materials in aerospace and high-end equipment manufacturing fields with broad application prospects. Applying titanium-aluminum alloys to high-end components can effectively reduce equipment weight, decrease the consumption of precious metal materials, and control manufacturing costs, demonstrating significant economic and engineering application value. However, traditional titanium-aluminum alloys have inherent performance limitations: low room-temperature plasticity and insufficient high-temperature oxidation and creep resistance, which greatly restricts their widespread use in high-end critical load-bearing components in aerospace.
[0003] Currently, the industry commonly uses doping with alloying elements to modify titanium-aluminum alloys. Commonly used modifying elements include niobium, chromium, molybdenum, boron, and silicon. This modification method relies on adjusting the type and amount of elements to reconstruct the microstructure, thereby improving the alloy's mechanical properties. However, the existing composition ratios of titanium-aluminum alloys have not reached an optimal state, resulting in limited modification effects. They generally suffer from poor mechanical property stability, an imbalance between strength and toughness, and weak corrosion resistance, failing to meet the stringent standards for high strength, high stability, and high weather resistance required for core aerospace components. Summary of the Invention
[0004] The purpose of this invention is to provide a titanium-aluminum alloy, its preparation method, and alloy materials, aiming to solve the technical problems of unstable mechanical properties, poor strength-toughness synergy, and insufficient corrosion resistance caused by poor component ratios in existing titanium-aluminum alloys.
[0005] To achieve the above objectives, the present invention provides a titanium-aluminum alloy, which, by atomic percentage, comprises the following components: Al: 45–48 at.%, V: 0–2 at.%, Cr: 0–5 at.%, Mn: 0–3.5 at.%, Nb: 0–5 at.%, Ta: 0–5 at.%, Mo: 0–2 at.%, W: 0–2 at.%, Hf: 0–2 at.%, Zr: 0–2 at.%, Si: 0–0.8 at.%, B: 0–0.8 at.%, C: 0–0.3 at.%, O: 0–0.3 at.%; the balance being Ti and unavoidable harmful impurities; the unavoidable harmful impurities include Fe, Ni, Pb, Sn, and S, and the total atomic percentage content of the harmful impurities is ≤0.5 at.%.
[0006] The microstructure of the titanium-aluminum alloy consists of equiaxed crystals and lamellar structures, with the average size of the equiaxed crystals ≤20μm and the average spacing between the lamellar structures ≤400nm.
[0007] As a preferred embodiment, the chemical composition of the titanium-aluminum alloy, by atomic percentage, preferably satisfies: Al 46~47.5 at.%, B 0.1~0.5 at.%, Si 0.2~0.6 at.%, total Nb and Ta content 2~5 at.%, O≤0.15 at.%, C≤0.15 at.%; the corresponding microstructure preferably satisfies: equiaxed crystal size 5~15μm, interlamellar spacing 100~300nm, and Al element segregation coefficient 1.01~1.15.
[0008] As a further preferred embodiment, the chemical composition of the titanium-aluminum alloy specifically satisfies: Al 46~47 at.%, Nb 2~4 at.%, Cr 2~3 at.%, Mn 1~2.5 at.%, Si 0.2~0.5 at.%, B 0.1~0.2 at.%, C 0.1~0.2 at.%, and the contents of Mo, W, Hf, and Zr are each 0.5~1.5 at.%.
[0009] The present invention also provides a method for preparing the above-mentioned titanium-aluminum alloy, comprising the following steps: S1 Raw Material Selection: Use sponge titanium and aluminum blocks with a purity ≥99.9%; when the alloy contains at least one element from V, Cr, Mn, Nb, Ta, Mo, W, Hf, Zr, Si, B, and C, use a metallic element or titanium-aluminum based master alloy with a purity ≥99.9%; when the content of the corresponding element is 0 at.%, no corresponding raw material is added.
[0010] S2 Ingredient Mixing and Vacuum Drying: Weigh all raw materials according to the formula, mix them in a vacuum mixer and then vacuum dry; Vacuum mixing: chamber vacuum degree ≤5×10^3Pa, speed 150~250r / min, mixing for 2~4h; Vacuum drying: temperature 160~200℃, heat preservation for 1~2h, and chamber vacuum degree ≤5×10^3Pa after drying.
[0011] S3 electrode block pressing: The powder is wrapped with high-purity aluminum foil with a thickness of 0.1 to 0.3 mm and pressed into an 85±2 mm × 85±2 mm × 400±5 mm electrode block under a pressure of 100 to 300 MPa for 2 to 5 minutes.
[0012] S4 electrode butt welding: Tungsten inert gas (TIG) welding of butt electrode blocks, welding current 100-300A, voltage 10-15V, welding speed 2-5mm / s.
[0013] S5 Vacuum Consumable Arc Melting: The welding electrode is hoisted and aligned with a centering deviation of ≤1mm; the vacuum inside the furnace is ≤1×10^2Pa, and leak testing is performed for 30min; high-frequency arc initiation is performed, with an initial current of 1.5~3.0kA and the arc stabilized for 10~20s before increasing to the working current; the working current is 3.0~5.0kA, the voltage is 25~40V, the melting rate is 2.0~8.0kg / min, and high-purity argon gas with a purity of ≥99.99% is introduced, with a furnace pressure of 50~200Pa; after the ingot is turned over, it is remelted, and remelted a total of 3~5 times; after each remelting, the ingot is cooled to ≤100℃ at the core before the next melting is carried out; after melting, the ingot is slowly cooled under vacuum at a rate of 5~20℃ / min.
[0014] Furthermore, in step S5, the diameter of the consumable electrode is 80-120 mm.
[0015] S6 ingot cleaning and unloading: The ingot core is unloaded at ≤100℃, and the surface layer of 3-5mm is removed by turning.
[0016] S7 Homogenization heat treatment: Heat the ingot to 1100~1200℃ and hold for 8~12h, then air cool to room temperature to obtain titanium-aluminum alloy ingot blank; S8 Plastic Forming and Temperature Control: A composite spacer protective layer is laid between the outer wall of the titanium-aluminum alloy ingot blank and the inner surface of the casing, and the whole is sealed and encapsulated. The encapsulated titanium-aluminum alloy ingot blank is heated and kept at a constant temperature before being plastically extruded. After extrusion molding, low-speed temperature-controlled cooling is implemented to finally obtain a titanium-aluminum alloy with an average equiaxed crystal size ≤20μm and an average lamellar spacing ≤400nm.
[0017] As a preferred structure, the composite spacer protective layer has a total thickness of 3.0–5.0 mm and is composed of a double-layer structure: the inner layer is a high-silica glass fiber cloth with a temperature resistance of ≥1300℃ and a thickness of 1.0–2.0 mm, and the outer layer is a high-temperature glass lubricant for titanium-aluminum extrusion with a softening temperature of 800–1000℃ and a thickness of 2.0–3.0 mm; the double-layer structure is bonded together by a high-temperature glass lubricant coating and is seamlessly bonded to the titanium-aluminum alloy and the sheath.
[0018] More preferably, the optimized parameters of the composite spacer protective layer are: high silica glass fiber cloth with a temperature resistance ≥1350℃, glass lubricant softening temperature 850~950℃, and total thickness of the composite protective layer 3.5~4.5mm.
[0019] As a preferred embodiment, the sleeve is made of 304 stainless steel and includes a sleeve body, a front end cap, and a rear end cap; the sleeve body has a wall thickness of 5-15mm and an inner and outer wall roughness of Ra 2.5-4.0μm; the ratio of the thickness of the front and rear end caps to the outer diameter of the titanium-aluminum alloy is 0.25-0.80, and the outer edge of the caps has a 35°-55° chamfer; the front end cap has 1-2 vent holes with a diameter of 2.0-5mm; the caps and the sleeve body are circumferentially sealed and leak-free.
[0020] As preferred process parameters, the high-temperature extrusion and cooling process is as follows: the titanium-aluminum alloy is heated to 1250-1300℃, held for 3-6 hours, the extrusion ratio is 3.5-5.5, and the extrusion speed is 25-40 mm / s; high-purity argon gas is introduced for protection throughout the extrusion process, and after extrusion, the alloy is air-cooled to room temperature at a rate of 50-80℃ / h along with the cladding.
[0021] The present invention also provides a titanium-aluminum alloy material, which is prepared by the above-described titanium-aluminum alloy method.
[0022] Finally, this invention provides a high-strength, tough, corrosion-resistant, and creep-resistant titanium-aluminum alloy bar for aerospace applications, which is precision-machined from the aforementioned titanium-aluminum alloy material and is suitable for the demanding working conditions required in aerospace applications.
[0023] The beneficial effects of this invention are as follows: This invention discloses a titanium-aluminum alloy, its preparation method, and alloy materials. By optimizing the alloy composition ratio, customizing the preparation process, and improving the encapsulation extrusion molding process, the comprehensive performance of the titanium-aluminum alloy is optimized, making it suitable for high-end aerospace applications.
[0024] This invention precisely controls the core aluminum content of the alloy, matches a reasonable ratio of various alloying elements, limits the content of harmful impurities, avoids the damage of impurities to the alloy's crystal structure, and improves the alloy's strength, toughness, and corrosion resistance. Simultaneously, this invention strictly controls the alloy's grain size, lamellar spacing, and elemental segregation coefficient, improving the uniformity of the alloy's microstructure and mitigating performance fluctuations caused by component segregation, thus meeting the standards used in the aerospace field.
[0025] This invention employs high-purity raw materials and a systematic preparation process including vacuum powder mixing, high-temperature drying, dense briquetting, multi-cycle vacuum melting, gradient slow cooling, and homogenization heat treatment, with strict control over core process parameters at each stage. This complete preparation process improves upon traditional processes, addressing issues such as uneven raw material mixing, insufficient melting, porosity and segregation in titanium-aluminum alloy ingots, and structural defects. It eliminates thermal stress and internal defects in titanium-aluminum alloy ingots, resulting in a titanium-aluminum alloy with uniform composition, dense structure, and stable performance, providing a fundamental titanium-aluminum alloy guarantee for subsequent high-precision extrusion molding.
[0026] This invention innovatively incorporates a double-layer composite protective layer, optimizing the structural dimensions of the stainless steel sheath and the extrusion molding process parameters. The double-layer composite protective layer simultaneously provides interface isolation, molding lubrication, and high-temperature oxidation prevention, effectively solving molding defects such as titanium-aluminum alloy adhesion, surface scratches, interface oxidation, and poor molding accuracy during extrusion molding. Furthermore, the optimized sheath structure and extrusion process refine the alloy grains and optimize the microstructure, effectively improving the molding accuracy, microstructure uniformity, and mechanical properties of titanium-aluminum alloy profiles.
[0027] This invention achieves a complete titanium-aluminum alloy preparation and molding technology system through the synergistic adaptation of three core technologies: alloy composition design, titanium-aluminum alloy preparation process, and encapsulated extrusion molding process. This system can stably produce high-strength, high-toughness, wear-resistant, fatigue-resistant, and corrosion-resistant titanium-aluminum alloy profiles, which can be applied to high-temperature wear-resistant structural components in aerospace. Attached Figure Description
[0028] Figure 1 This is a photograph of the finished titanium-aluminum alloy product of the present invention; Figure 2 This is a schematic diagram of the extrusion of the titanium-aluminum alloy of the present invention; Figure 3 This is a schematic diagram of the extruded cross-section of the titanium-aluminum alloy of the present invention; Figure 4 This is a photograph of the titanium-aluminum alloy and 304 stainless steel casing of the present invention. Figure 5 This is a physical image of a titanium-aluminum alloy with a composite spacer protective layer as described in this invention.
[0029] Markings in the diagram: 1—Titanium-aluminum alloy; 2—High-silica glass fiber cloth; 3—304 stainless steel sheath. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the protection scope of the present invention.
[0031] In existing technologies, titanium-aluminum alloys possess advantages such as low density, high specific strength, and high temperature resistance, making them valuable for applications in aerospace and high-end equipment. However, existing titanium-aluminum alloys generally suffer from low room temperature plasticity, poor high-temperature oxidation resistance, and insufficient high-temperature creep resistance. Conventional alloying element modification schemes suffer from poor component ratio compatibility, leading to an imbalance in alloy strength and toughness, insufficient mechanical stability, and inadequate corrosion resistance. Furthermore, traditional cladding extrusion molding processes suffer from poor compatibility between titanium-aluminum alloys and 304 stainless steel cladding, easy formation of brittle intermetallic compounds at high-temperature interfaces, and insufficient precision in process parameter control. These issues easily result in uneven profile deformation, surface defects, internal microstructure segregation, and substandard performance, hindering the large-scale engineering application of high-performance titanium-aluminum alloys in high-end load-bearing components for aerospace applications.
[0032] To overcome the shortcomings of existing technologies, this invention provides a titanium-aluminum alloy, its preparation method, and alloy materials. By precisely defining the range of multi-element alloy components, optimizing the entire high-vacuum preparation process, and employing a double-layer composite spacer protective layer encapsulation extrusion molding process, the invention solves the performance shortcomings and forming process defects of traditional titanium-aluminum alloys. This results in a titanium-aluminum alloy with uniform and controllable microstructure and stable and excellent performance, which can meet the harsh high-temperature and high-pressure alternating load service conditions of aerospace and is suitable for large-scale and repeatable preparation.
[0033] The titanium-aluminum alloy of this invention is composed of the following components by atomic percentage: Al: 45-48 at.%, V: 0-2 at.%, Cr: 0-5 at.%, Mn: 0-3.5 at.%, Nb: 0-5 at.%, Ta: 0-5 at.%, Mo: 0-2 at.%, W: 0-2 at.%, Hf: 0-2 at.%, Zr: 0-2 at.%, Si: 0-0.8 at.%, B: 0-0.8 at.%, C: 0-0.3 at.%, O: 0-0.3 at.%; the balance being Ti and unavoidable harmful impurities; the unavoidable harmful impurities include Fe, Ni, Pb, Sn, and S, and the total atomic percentage content of the unavoidable harmful impurities is ≤0.5 at.%; the microstructure of the titanium-aluminum alloy consists of equiaxed grain structure and lamellar structure, the average grain size of the equiaxed grains is ≤20μm, and the average interlamellar spacing of the lamellar structure is ≤400nm.
[0034] This invention, by defining the above-mentioned precise alloy composition system and combining the whole-process high-vacuum sealed preparation process with the encapsulated extrusion molding process with a double-layer composite spacer protective layer, precisely controls the dual-state microstructure of titanium-aluminum alloys. This effectively improves the technical problems of traditional titanium-aluminum alloys, such as imbalance of strength and toughness, uneven microstructure, weak high-temperature oxidation and creep resistance, and many extrusion molding defects. It also simultaneously improves the alloy's room temperature plasticity, high-temperature service performance, wear resistance, fatigue resistance, and corrosion resistance, resulting in excellent product performance consistency and process repeatability.
[0035] Example 1: Verification example of the composition ratio range of titanium-aluminum alloy.
[0036] Example of lower limit of ratio: This embodiment provides a titanium-aluminum alloy with the following chemical composition by atomic percentage: Al: 45 at.%, V: 0 at.%, Cr: 0 at.%, Mn: 0 at.%, Nb: 0 at.%, Ta: 0 at.%, Mo: 0 at.%, W: 0 at.%, Hf: 0 at.%, Zr: 0 at.%, Si: 0 at.%, B: 0 at.%, C: 0 at.%, O: 0 at.%; the balance being Ti and unavoidable harmful impurities, with the total atomic percentage content of unavoidable harmful impurities ≤ 0.5 at.%. The microstructure of this titanium-aluminum alloy satisfies the following: average equiaxed grain size ≤ 20 μm, and average interlamellar spacing ≤ 400 nm.
[0037] Combined with appendix Figure 1 To be continued Figure 5 The preparation method of the titanium-aluminum alloy in this embodiment includes the following process steps with specific process parameters: (1) Raw material selection: Sponge titanium and aluminum blocks with a purity of ≥99.9% are selected. No other alloying elements are added in this embodiment, and no corresponding intermediate alloys and elemental raw materials are required. The purity of all raw materials meets the standard requirements.
[0038] (2) Ingredient mixing and vacuum drying: Weigh the raw materials accurately according to the ratio and put them into the vacuum mixer. The vacuum degree of the chamber is ≤5×10Pa, the rotation speed is 200r / min, and the mixing time is 3h. After the mixing is completed, vacuum dry the raw materials at a drying temperature of 160℃ and keep warm for 1.5h. After drying, the vacuum degree of the chamber is maintained at ≤5×10Pa to completely remove the adsorbed water vapor and free gas of the raw materials.
[0039] (3) Electrode block pressing: The mixed powder is wrapped with high-purity aluminum foil with a thickness of 0.2mm and pressed into a regular and dense electrode block of 85mm×85mm×400mm under a pressure of 200MPa for 3min.
[0040] (4) Electrode butt welding: Tungsten inert gas welding is used for butt electrode blocks. The welding current is 200A, the voltage is 12V, and the welding speed is 3mm / s. After welding, the electrode butt is flat, the coaxiality deviation is ≤1mm, and the weld is free of porosity, cracks, and slag inclusions.
[0041] (5) Vacuum self-consuming arc melting: The welding electrode is hoisted and aligned, with an alignment deviation of ≤1mm; the vacuum degree in the furnace is evacuated to ≤1×10Pa, and leak is checked for 30min; high-frequency arc is initiated, with an initial current of 2.0kA and the arc is stabilized for 15s before being increased to the working current of 4.0kA, with a melting voltage of 32V and a melting rate of 5.0kg / min; high-purity argon gas with a purity of ≥99.99% is introduced into the furnace to maintain the furnace pressure at 120Pa; the titanium-aluminum alloy ingot is flipped and remelted, with a total of 4 melting times. After each melting, the temperature of the core of the titanium-aluminum alloy ingot is ≤100℃ before the next melting is carried out; after melting, it is slowly cooled in vacuum at a rate of 12℃ / min; in this embodiment, the diameter of the melting electrode is 100mm.
[0042] (6) Cleaning and unloading of titanium-aluminum alloy ingots: After the core temperature of the titanium-aluminum alloy ingot is ≤100℃, it is unloaded from the furnace and the surface 4mm of oxidation and loose defects are removed by turning.
[0043] (7) Homogenization heat treatment: Heat the titanium-aluminum alloy ingot to 1100℃, hold for 10h, and air cool to room temperature to eliminate ingot composition segregation and residual stress of titanium-aluminum alloy casting.
[0044] (8) Plastic forming and temperature control: A double-layer composite spacer protective layer is laid between the outer wall of the titanium-aluminum alloy blank and the inner surface of the 304 stainless steel sheath and sealed as a whole; the total thickness of the double-layer composite spacer protective layer is 4.0 mm, the inner layer is 1.5 mm high silica glass fiber cloth 2 with a temperature resistance of ≥1350℃, and the outer layer is 2.5 mm high temperature glass lubricant for titanium-aluminum extrusion with a softening temperature of 900℃. The double-layer structure is bonded together without gaps by high temperature glass lubricant coating; the high temperature glass lubricant is a borosilicate high temperature glass lubricant commonly used in the extrusion processing of titanium-aluminum alloy sheaths, and it can be achieved by meeting the corresponding softening temperature index. The 304 stainless steel sheath body has a wall thickness of 10 mm, an inner and outer wall roughness Ra of 3.0 μm, a front and rear end cap thickness to alloy outer diameter ratio of 0.5, a 45° chamfer on the outer edge of the cap, a 3 mm diameter vent hole on the front end cap, and a circumferential seal between the cap and the 304 stainless steel sheath body with no leakage.
[0045] After encapsulation, the titanium-aluminum alloy blank is heated to 1280℃ and held for 4 hours. The extrusion ratio is 4.5 and the extrusion speed is 32mm / s. High-purity argon gas is introduced for protection throughout the extrusion process. After extrusion, the titanium-aluminum alloy blank is air-cooled to room temperature at a rate of 65℃ / h along with a 304 stainless steel sheath to complete the plastic forming of the titanium-aluminum alloy.
[0046] The finished product test results of this embodiment are as follows: the average grain size of equiaxed crystals is 18 μm, the average interlamellar spacing of lamellar structure is 380 nm, and the total atomic percentage content of unavoidable harmful impurities is 0.32 at.%.
[0047] Preferred intermediate ratio example: This embodiment represents the optimal formulation of the invention, with the content of each element falling within the preferred range. The chemical composition, expressed as atomic percentage, is as follows: Al: 46.8 at.%, V: 1.0 at.%, Cr: 2.5 at.%, Mn: 2.0 at.%, Nb: 3.0 at.%, Ta: 2.0 at.%, Mo: 1.0 at.%, W: 1.0 at.%, Hf: 1.0 at.%, Zr: 1.0 at.%, Si: 0.4 at.%, B: 0.3 at.%, C: 0.15 at.%, O: 0.12 at.%; the balance being Ti and unavoidable harmful impurities, with the total atomic percentage content of unavoidable harmful impurities ≤ 0.4 at.%.
[0048] In this embodiment, the alloying elements are synergistically proportioned, resulting in optimal controllability of the microstructure.
[0049] The specific preparation process steps are as follows: (1) Raw material selection: Select sponge titanium, aluminum blocks and corresponding intermediate alloys with a purity of ≥99.9%, and weigh each raw material component accurately according to the ratio.
[0050] (2) Ingredient mixing and vacuum drying: Vacuum mixing vacuum degree 4×10Pa, rotation speed 220r / min, mixing for 3.5h; vacuum drying temperature 180℃, heat preservation for 1.5h, and the vacuum degree of the chamber after drying ≤5×10Pa.
[0051] (3) Electrode block pressing: The powder is wrapped with 0.25mm high-purity aluminum foil and pressed into standard-sized electrode blocks under 250MPa pressure for 4 minutes.
[0052] (4) Electrode butt welding: welding current 220A, voltage 13V, welding speed 4mm / s, electrode butt coaxiality deviation ≤1mm, and weld formation good.
[0053] (5) Vacuum self-consuming arc melting: the vacuum degree in the furnace is ≤1×10Pa, the leak detection is 30min; the initial current is 2.5kA and the arc is stabilized for 18s, the working current is 4.5kA, the voltage is 35V, and the melting rate is 6.0kg / min; the argon pressure in the furnace is 150Pa, the total number of melting times is 4, and the temperature of the core of the titanium-aluminum alloy ingot is ≤100℃ between each melting; the cooling rate after melting is 15℃ / min, and the diameter of the melting electrode is 100mm.
[0054] (6) Cleaning of titanium-aluminum alloy ingots: After the titanium-aluminum alloy ingots are cooled and taken out of the furnace, the surface 4mm defect area is removed by turning.
[0055] (7) Homogenization heat treatment: keep at 1150℃ for 11h, then air cool to room temperature.
[0056] (8) Plastic forming and temperature control treatment: The total thickness of the double-layer composite spacer protective layer is 4.0mm, the inner layer is 2.0mm high silica glass fiber cloth 2 (temperature resistance ≥1350℃), and the outer layer is 2.0mm high temperature glass lubricant (softening temperature 900℃); the 304 stainless steel sheath has a wall thickness of 12mm, the inner and outer wall roughness Ra3.5μm, the end cap thickness-to-outer diameter ratio is 0.6, 45° chamfer, 4mm vent hole at the front end, and is sealed without leakage; the high temperature glass lubricant is a borosilicate-based high temperature glass lubricant commonly used in the extrusion processing of titanium-aluminum alloy sheaths, and it can be achieved by meeting the corresponding softening temperature index.
[0057] The alloy was heated to 1290℃ and held for 5 hours. The extrusion ratio was 5.0 and the extrusion speed was 35 mm / s. Argon gas protection was used throughout the process. After extrusion, the alloy was air-cooled to room temperature at a rate of 70℃ / h with a 304 stainless steel sheath.
[0058] The finished product test results of this embodiment are as follows: the average grain size of equiaxed crystals is 10 μm, the average interlamellar spacing of lamellar structure is 200 nm, the total atomic percentage content of unavoidable harmful impurities is 0.28 at.%, the structure is excellent, and the comprehensive mechanical properties and high-temperature service performance are optimal.
[0059] Example of upper limit ratio: In this embodiment, the chemical composition, by atomic percentage, is as follows: Al: 48 at.%, V: 2 at.%, Cr: 5 at.%, Mn: 3.5 at.%, Nb: 5 at.%, Ta: 5 at.%, Mo: 2 at.%, W: 2 at.%, Hf: 2 at.%, Zr: 2 at.%, Si: 0.8 at.%, B: 0.8 at.%, C: 0.3 at.%, O: 0.3 at.%; the balance is Ti and unavoidable harmful impurities, with the total atomic percentage content of unavoidable harmful impurities ≤ 0.5 at.%.
[0060] The specific preparation process steps are as follows: (1) Raw material selection: Select sponge titanium, aluminum blocks and corresponding high-content alloy intermediates with a purity of ≥99.9% and weigh them in precise proportion.
[0061] (2) Ingredient mixing and vacuum drying: Vacuum mixing: vacuum degree 3×10Pa, rotation speed 240r / min, mixing for 4h; vacuum drying temperature 200℃, heat preservation for 2h, vacuum degree meets the standard after drying.
[0062] (3) Electrode block pressing: Wrapped in 0.3mm high-purity aluminum foil, press for 5 minutes at 280MPa pressure to form a standard electrode block.
[0063] (4) Electrode welding: welding current 280A, voltage 14V, welding speed 4.5mm / s, electrode docking accuracy meets the standard.
[0064] (5) Vacuum self-consuming arc melting: initial current 3.0kA, arc stabilization for 20s, working current 5.0kA, voltage 38V, melting rate 7.5kg / min; argon pressure in furnace 180Pa, total melting times 5 times, cooling rate 18℃ / min, melting electrode diameter 110mm.
[0065] (6) Cleaning of titanium-aluminum alloy ingots: After exiting the furnace, the surface 5mm defect area is removed by turning.
[0066] (7) Homogenization heat treatment: keep at 1200℃ for 12h, then air cool to room temperature.
[0067] (8) Plastic forming and temperature control treatment: The total thickness of the double-layer composite spacer protective layer is 4.5mm, the inner layer is 2.0mm high silica glass fiber cloth with a temperature resistance of 1350℃, and the outer layer is 2.5mm glass lubricant with a softening temperature of 950℃; the 304 stainless steel sheath has a wall thickness of 15mm, a roughness Ra of 4.0μm, an end cap outer diameter ratio of 0.7, a 50° chamfer, a 4mm vent hole at the front end, and is sealed without leakage; the high temperature glass lubricant is a borosilicate-based high temperature glass lubricant commonly used in the extrusion processing of titanium-aluminum alloy sheaths, and it can be achieved by meeting the corresponding softening temperature index.
[0068] The alloy was heated to 1300℃ and held for 6 hours. The extrusion ratio was 5.5 and the extrusion speed was 38 mm / s. Argon gas protection was used throughout the process. After extrusion, the alloy was air-cooled to room temperature at a rate of 75℃ / h.
[0069] The finished product test results of this embodiment are as follows: the average grain size of equiaxed crystals is 19 μm, the average interlamellar spacing of lamellar structure is 390 nm, and the total atomic percentage content of unavoidable harmful impurities is 0.45 at.%.
[0070] Example 2: Principle and apparatus description of the encapsulation extrusion molding process: The core forming process of this invention is a sheathed extrusion molding process. The core principle is as follows: a 304 stainless steel sheath 3 is sealed around the titanium-aluminum alloy 1 blank. The constraint effect of the 304 stainless steel sheath 3 constructs a uniform triaxial compressive stress field during extrusion, reducing high-temperature heat loss from the alloy and inhibiting the initiation and propagation of microcracks. This fundamentally improves the inherent defects of titanium-aluminum alloys, such as poor room-temperature plasticity and difficulty in high-temperature forming. Simultaneously, by setting a double-layer composite spacer between the titanium-aluminum alloy 1 and the 304 stainless steel sheath 3, direct contact between the heterogeneous interfaces is completely isolated, preventing the diffusion of elements at high temperatures and the formation of brittle intermetallic compounds. This layer also serves to lubricate and reduce drag, buffer extrusion stress, and synchronize deformation rates, solving problems such as sheath tearing, uneven profile deformation, interface defects, and microstructure segregation in traditional processes.
[0071] Combined with appendix Figure 2 To be continued Figure 5As shown, the extrusion molding apparatus of this invention consists of a horizontal extruder, a precision temperature-controlled box furnace, a 304 stainless steel sealing sleeve 3, a titanium-aluminum alloy blank 1, a double-layer composite spacer protective layer, a high-purity argon inert gas protection device, and a real-time temperature monitoring and control system: 1. Precision temperature-controlled box furnace: temperature control accuracy ±5℃, enabling segmented heating, precise constant temperature, and gradient cooling to ensure uniform overall alloy temperature and avoid local microstructure differences; 2. Horizontal extruder: extrusion speed steplessly adjustable from 25 to 40 mm / s, adapting to the deformation requirements of alloys with different proportions, ensuring profile dimensional accuracy and microstructure uniformity; 3. High-purity argon inert gas protection device: ≥99.99% high-purity argon gas is introduced throughout the process to create an oxygen-free atmosphere, preventing high-temperature oxidation and elemental loss of the alloy; 4. Real-time temperature monitoring and control system: closed-loop control of temperature parameters throughout the process to ensure process stability and repeatability.
[0072] This invention achieves high-precision, defect-free, and large-scale stable forming of titanium-aluminum alloy profiles by optimizing the structural parameters of the 304 stainless steel sheath, the double-layer composite spacer protective layer system, and the precise extrusion process and temperature control, thus solving many of the shortcomings of existing forming technologies.
[0073] Example 3: Verification of Gradient Process Parameters Across the Entire Range This embodiment performs full-coverage verification by selecting lower limit, optimal, and upper limit gradient parameters for all process parameter ranges to ensure that qualified products can be stably reproduced in all process ranges.
[0074] Example of lower limit of process parameters: The titanium-aluminum alloy of this embodiment has the following chemical composition by atomic percentage: Al: 45 at.%, V: 0 at.%, Cr: 0 at.%, Mn: 0 at.%, Nb: 0 at.%, Ta: 0 at.%, Mo: 0 at.%, W: 0 at.%, Hf: 0 at.%, Zr: 0 at.%, Si: 0 at.%, B: 0 at.%, C: 0 at.%, O: 0 at.%; the balance is Ti and unavoidable harmful impurities, with the total atomic percentage content of unavoidable harmful impurities ≤ 0.5 at.%. Matching process lower limit parameters: vacuum powder mixing speed 150 r / min, mixing for 4 h; vacuum drying temperature 160℃, holding for 1 h; aluminum foil thickness 0.1 mm; pressing pressure 100 MPa, holding for 2 min; welding current 100 A, voltage 10 V, welding speed 2 mm / s; vacuum self-consuming arc melting initial current 1.5 kA, working current 3.0 kA, voltage 25 V, melting rate 2.0 kg / min, furnace argon pressure 50 Pa, melting times 3 times, cooling rate 5 ℃ / min; homogenization heat treatment 1100℃, heat preservation 8h; total thickness of double-layer composite spacer protective layer 3.5mm (inner layer 1.0mm high silica fiber cloth 2 + outer layer 2.5mm high temperature glass lubricant); 304 stainless steel sheath wall thickness 5mm, roughness Ra 2.5μm, end cap outer diameter ratio 0.25, 35° chamfer, 2.0mm vent hole; extrusion temperature 1250℃, heat preservation 3h, extrusion ratio 3.5, extrusion speed 25mm / s; cooling rate 50℃ / h.
[0075] Finished product inspection: The average grain size of equiaxed crystals is 18μm, the average interlamellar spacing is 360nm, the profiles are free of cracks and segregation, and the performance fully meets the standards.
[0076] Optimal Example of Process Parameters: The optimal alloy ratio and process parameters were selected: vacuum powder mixing speed 200 r / min, mixing for 3 h; vacuum drying temperature 180℃, holding for 1.5 h; 0.2 mm aluminum foil, holding pressure at 200 MPa for 3 min; welding current 200 A, voltage 12 V, speed 3.5 mm / s; vacuum self-consuming arc melting initial current 2.0 kA, working current 4.0 kA, voltage 32 V, melting rate 5.0 kg / min, argon pressure 120 Pa, melting 4 times, cooling rate 12℃ / min; homogenization heat treatment at 1150℃ for 10 h; double-layer composite spacer protective layer 4.0 mm; 304 stainless steel sheath wall thickness 10 mm, Ra 3.0 μm, end cap ratio 0.5, 45° chamfer, 3.5 mm vent hole; holding at 1280℃ for 4.5 h, extrusion ratio 4.5, speed 32 mm / s; cooling at 65℃ / h.
[0077] Finished product inspection: The average grain size of the equiaxed crystals is 16μm, the average interlamellar spacing is 320nm, the structure is dense and uniform, and the overall performance is optimal.
[0078] Example of upper limit of process parameters: The formula adopts the upper limit ratio of the components and matches the upper limit parameters of the process: vacuum powder mixing speed 250r / min, mixing for 2h; vacuum drying temperature 200℃, holding for 2h; 0.3mm aluminum foil, holding pressure of 300MPa for 5min; welding current 300A, voltage 15V, speed 5mm / s; vacuum self-consuming arc melting initial current 3.0kA, working current 5.0kA, voltage 40V, melting rate 8.0kg / min, argon pressure 200Pa, melting 5 times, cooling rate 20℃ / min; homogenization heat treatment at 1200℃ for 8h; double-layer composite spacer protective layer 4.5mm; 304 stainless steel sheath wall thickness 15mm, Ra 4.0μm, end cap ratio 0.8, 55° chamfer, 5mm vent hole; holding at 1300℃ for 6h, extrusion ratio 5.5, speed 40mm / s; cooling at 80℃ / h.
[0079] Finished product inspection: The average grain size of equiaxed crystals is 14μm, the average interlamellar spacing of lamellar structure is 280nm, and there are no molding defects.
[0080] Example 4: Performance Verification Example of Alloy Rods for Aerospace Applications: This embodiment uses the preferred proportions and complete preparation process of the present invention to prepare high-strength, tough, corrosion-resistant, and creep-resistant titanium-aluminum alloy bar for aerospace applications, suitable for harsh service scenarios such as high-temperature load-bearing components of aero-engines and heavy-duty components of aircraft.
[0081] Alloy composition (atomic percentage): Al: 47.0 at.%, Nb: 2.2 at.%, Ta: 1.8 at.%, Si: 0.3 at.%, B: 0.12 at.%, balance is Ti and unavoidable harmful impurities, the total atomic percentage content of unavoidable harmful impurities is ≤0.3 at.%, and the purity of raw materials is ≥99.9%.
[0082] The preparation process strictly follows the procedures: vacuum arc melting, homogenization heat treatment, extrusion with a 304 stainless steel sheath with a double-layer composite spacer protective layer, temperature-controlled cooling, and precision machining to produce finished bars. The microstructure is characterized by an average equiaxed grain size of 12μm and an average lamellar spacing of 220nm, meeting the core performance requirements.
[0083] Performance tests were conducted using national standard testing methods, and the performance comparison with traditional titanium-aluminum alloys is as follows: 1. Room temperature plasticity: The room temperature elongation of the alloy of this invention is 4.8%, while that of the traditional alloy is 2.1%, significantly improving room temperature brittleness and greatly enhancing processability; 2. High temperature oxidation resistance: After 100 hours of oxidation testing at 850℃, the oxidation weight gain is 0.028 mg / (cm²·h), far superior to the 0.095 mg / (cm²·h) of the traditional alloy; 3. High temperature creep resistance: Under a load of 200 MPa at 850℃, the creep fracture life is 112 hours, significantly improved compared to the 36 hours of the traditional alloy; 4. Wear resistance and fatigue resistance: The high temperature wear rate is reduced by 42.5% compared to the traditional alloy, and under a high-cycle fatigue load of 300 MPa, the number of fatigue cycles can reach 1.2 × 10⁻⁶, with no crack initiation or failure.
[0084] In summary, the titanium-aluminum alloy 1 and alloy rods prepared by this invention achieve uniform and controllable microstructure and stable and excellent performance through precise component ratio and whole-process process optimization. This effectively solves the problems of poor room temperature plasticity, insufficient high-temperature oxidation resistance, creep resistance and fatigue resistance of traditional titanium-aluminum alloys, and fully meets the needs of large-scale engineering applications in high-end and demanding aerospace conditions.
[0085] The above are merely preferred embodiments of the present invention and do not limit the scope of the patent. Any equivalent structural or procedural transformations made based on the description and drawings of the present invention, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.
Claims
1. A titanium-aluminum alloy, characterized in that, It is composed of the following components by atomic percentage: Al: 45–48 at.%, V: 0–2 at.%, Cr: 0–5 at.%, Mn: 0–3.5 at.%, Nb: 0–5 at.%, Ta: 0–5 at.%, Mo: 0–2 at.%, W: 0–2 at.%, Hf: 0–2 at.%, Zr: 0–2 at.%, Si: 0–0.8 at.%, B: 0–0.8 at.%, C: 0–0.3 at.%, O: 0–0.3 at.%; The balance is Ti and unavoidable harmful impurities; The unavoidable harmful impurities include Fe, Ni, Pb, Sn, and S, and the total atomic percentage content of the unavoidable harmful impurities is ≤0.5 at.%. The microstructure of the titanium-aluminum alloy consists of equiaxed crystals and lamellar structures, with the average size of the equiaxed crystals ≤20μm and the average spacing between the lamellar structures ≤400nm.
2. A method for preparing the titanium-aluminum alloy according to claim 1, characterized in that, The method includes the following steps: S1 Raw Material Selection: Use sponge titanium and aluminum blocks with a purity ≥99.9%; when the alloy contains at least one element from V, Cr, Mn, Nb, Ta, Mo, W, Hf, Zr, Si, B, C, and O, use a metallic element or titanium-aluminum based master alloy with a purity ≥99.9%; when the content of the corresponding element is 0 at.%, no corresponding raw material is added. S2 Ingredient Mixing and Vacuum Drying: Weigh all raw materials according to the formula, mix them in a vacuum mixer and then vacuum dry; Vacuum mixing: Chamber vacuum degree ≤5×10⁻³Pa, speed 150~250r / min, mixing for 2~4h; Vacuum drying: Temperature 160~200℃, heat preservation for 1~2h, after drying, chamber vacuum degree ≤5×10⁻³Pa; S3 electrode block pressing: High-purity aluminum foil with a thickness of 0.1 to 0.3 mm is used to wrap the powder, and the pressure is maintained at 100 to 300 MPa for 2 to 5 minutes to press it into an electrode block of 85±2 mm × 85±2 mm × 400±5 mm. S4 electrode butt welding: TIG welding of butt electrode blocks, welding current 100~300A, voltage 10~15V, welding speed 2~5mm / s; S5 Vacuum Consumable Arc Melting: Welding electrode hoisting and centering, centering deviation ≤1mm; furnace vacuum ≤1×10⁻²Pa, leak detection for 30min; high-frequency arc ignition, initial current 1.5~3.0kA, arc stabilization for 10~20s, then increasing to working current; working current 3.0~5.0kA, voltage 25~40V, melting rate 2.0~8.0kg / min, high-purity argon gas with purity ≥99.99% introduced, furnace pressure 50~200Pa; after ingot flipping, remelting is performed, total melting times are 3~5 times; after each melting, cooling to ingot core ≤100℃ before the next melting is carried out; after melting, ingot is slowly cooled under vacuum at a rate of 5~20℃ / min; S6 ingot cleaning and unloading: The core of the ingot is ≤100℃ when it is unloaded from the furnace, and the surface layer of 3-5mm is removed by turning. S7 Homogenization heat treatment: Heat the ingot to 1100~1200℃ and hold for 8~12h, then air cool to room temperature to obtain titanium-aluminum alloy ingot blank; S8 Plastic Forming and Temperature Control: A composite spacer protective layer is laid between the outer wall of the titanium-aluminum alloy ingot blank and the inner surface of the casing, and the whole is sealed and encapsulated. The encapsulated titanium-aluminum alloy ingot blank is heated and kept at a constant temperature before being plastically extruded. After extrusion molding, low-speed temperature-controlled cooling is implemented to finally obtain a titanium-aluminum alloy with an average equiaxed crystal size ≤20μm and an average lamellar spacing ≤400nm.
3. The preparation method according to claim 2, characterized in that, In step S5, the diameter of the consumable electrode is 80-120 mm.
4. The method according to claim 2, characterized in that, The composite spacer protective layer has a total thickness of 3.0–5.0 mm and is composed of a double-layer structure bonded together. The inner layer is a high-silica glass fiber cloth with a temperature resistance of ≥1300℃ and a thickness of 1.0~2.0mm, and the outer layer is a high-temperature glass lubricant for titanium-aluminum extrusion with a softening temperature of 800~1000℃ and a thickness of 2.0~3.0mm. The double-layer structure is bonded together by a high-temperature glass lubricating coating, and fits seamlessly with the titanium-aluminum alloy ingot blank and the cladding.
5. The method according to claim 4, characterized in that, The optimized parameters for the composite spacer protective layer are: high silica glass fiber cloth with a temperature resistance ≥1350℃, glass lubricant softening temperature 850~950℃, and total thickness of the composite protective layer 3.5~4.5mm.
6. The method according to claim 2, characterized in that, The sleeve is made of 304 stainless steel and includes a sleeve body, a front cover, and a rear cover. The sheath body has a wall thickness of 5–15 mm and an inner and outer wall roughness of Ra 2.5–4.0 μm; The ratio of the thickness of the front and rear end caps to the outer diameter of the titanium-aluminum alloy is 0.25 to 0.80, and the outer edge of the caps has a chamfer of 35° to 55°. The front end cap has 1 to 2 vent holes with a diameter of 2.0 to 5 mm; The cap and the main body of the casing are sealed together with a circumferential seam, ensuring no leakage.
7. The method according to claim 2, characterized in that, The high-temperature extrusion and cooling process parameters include: The heating temperature of the titanium-aluminum alloy is 1250-1300℃, the holding time is 3-6h, the extrusion ratio is 3.5-5.5, and the extrusion speed is 25-40mm / s. High-purity argon gas was introduced for protection throughout the extrusion process, and after extrusion, the extrusion was air-cooled to room temperature along with the casing at a rate of 50-80℃ / h.
8. A titanium-aluminum alloy material, characterized in that, It is prepared by the preparation method described in any one of claims 2 to 7.
9. A high-strength, high-toughness, corrosion-resistant, and creep-resistant titanium-aluminum alloy rod for aerospace applications, characterized in that... It is prepared from the titanium-aluminum alloy material described in claim 8.